Launch! - Duffy, Scott (Recorded Books, 2014)
A serial entrepreneur offers a plan for launching successful ventures About ninety-seven percent of a rocket' s fuel is used in the first three feet of its launch. The same is true in launching a new business, product, or service. Those first few steps are absolutely critical. Scott Duffy has developed a practical approach for turning your big idea into a thriving venture by focusing on the crucial period immediately before, during, and after opening your doors (literally or online). His approach is based on his experiences working with top entrepreneurs like Tony Robbins and Richard Branson, who taught him how to balance the two key sides of entrepreneurship: * The personal side, including personal finances, relationships, and health. * The business side, including raising capital, building teams, establishing partnerships, and closing sales. Duffy also draws on the true stories of other big names, such as Howard Schultz, Lou Holtz, and MC Hammer, to offer guidance on turning your vision into a full-fledged enterprise.